A dance in Donegal - Deibel, Jennifer, 1978- (Revell, a division of Baker Publishing Group, 2021)
"To fulfill her mother's dying wish, Moira Doherty moves from Boston to the rolling green hills of 1921 Ireland to teach in a village school. She doesn't expect to fall in love-or to uncover a scandalous family reputation her mother left behind years ago"--